“Art Meets Books”: A Co-produced Arts Pilot Project in Public Libraries - Val Huet (Creative Arts in Education and Therapy)
The “Art Meets Books” (AMB) pilot project is an innovative partnership involving a charity, Paintings in Hospitals, an art therapist (the present author), and public libraries. AMB delivers arts workshops within public libraries in economically deprived areas in London and the West Midlands and engages people who do not usually access art resources. Through outreach work within Further Education colleges, AMB also engages ethnically diverse participants. AMB integrates a co-production ethos and art-based reflexive practice. An evaluation conducted throughout the project showed that participants (N=49) reported positive experiences of the project. The evaluation identified issues to integrate into the project’s future delivery.